Asia bond monitor. (Metro Manila, Philippines Asian Development Bank, 2017)
Continued improvement in global economic prospects helped drive yields lower in most markets in emerging East Asia amid positive investor sentiment.
Keywords: Economic integration -- Asia; Sustainable development; Government securities -- Asia; Rate of return -- Asia; Electronic books